The Effect of Political Configuration on Legal Products: A Critical Study of Responsive Legal Concepts and Orthodox Conservative Law - Uul Fathur Rahmah (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2023)
This research discusses the political implications of the birth of legal products, focusing on the concept of responsive and orthodox conservative law. Discusses in depth both the political configuration and the legal character of the state system. This research uses a normative or doctrinal type of research which uses two approaches, namely a statutory approach and a conceptual approach. Consists of two problem formulations, namely 1) What is meant by the concept of responsive law and the resulting legal products? 2) What is meant by the concept of orthodox conservative law and the resulting legal products?. This research results that 1) Legal products (legislation) are greatly influenced by the political configuration in power, so that law is a political product which is a necessity in a country's system. Characteristics of responsive legal products include, participative creation, the content is aspirational and the content is limitative; 2) on the issue of the concept of orthodox conservative law, it has a centralistic-domistic character, its content is positivist-instrumental, its detailed content is open interpretive.